2019
DOI: 10.1016/j.watres.2018.11.068
|View full text |Cite
|
Sign up to set email alerts
|

N2 yields from monochloramine conversion by granular activated carbons are decisive for effective swimming pool water treatment

Abstract: Inorganic chloramines (mono-, di-and trichloramine) are formed in swimming pool water from the unintended reaction of free chlorine with ammonia that is introduced by bathers. Monochloramine is of particular interest as it is known to react further in pool water forming harmful DBPs, such carcinogenic N-nitrosodimethylamine (NDMA). During pool water treatment with granular activated carbon (GAC) filters, monochloramine is transformed by chemical reactions on the carbon surface to N 2 and ammonia. As ammonia is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 73 publications
(102 reference statements)
0
3
0
Order By: Relevance
“…Differences in the removal efficiencies between free chlorine and combined chlorine could be explained by the different reaction rates reported for their surface reaction with carbonaceous materials. 73,74 UV(LP) irradiation at the doses applied in this study (Table B.1 (SI)) reduced less-volatile DBPs and combined chlorine than did UV(MP) irradiation. These findings agree with previous results, where it has been shown that concentration levels of THMs could not be reduced by UV(LP) treatment, 75 while a minor mitigation of THMs in pool water has been observed for UV(MP) treatment.…”
Section: Dissolved Organic Matter Composition Under Stationary Condit...mentioning
confidence: 83%
See 1 more Smart Citation
“…Differences in the removal efficiencies between free chlorine and combined chlorine could be explained by the different reaction rates reported for their surface reaction with carbonaceous materials. 73,74 UV(LP) irradiation at the doses applied in this study (Table B.1 (SI)) reduced less-volatile DBPs and combined chlorine than did UV(MP) irradiation. These findings agree with previous results, where it has been shown that concentration levels of THMs could not be reduced by UV(LP) treatment, 75 while a minor mitigation of THMs in pool water has been observed for UV(MP) treatment.…”
Section: Dissolved Organic Matter Composition Under Stationary Condit...mentioning
confidence: 83%
“…The layer of PAC on the UF or in the sand filter removed a significant amount of combined chlorine (PAC–sand, 28.2 ± 7.4%; PAC–UF, 38.6 ± 12.6%) but also free chlorine (∼100%). Differences in the removal efficiencies between free chlorine and combined chlorine could be explained by the different reaction rates reported for their surface reaction with carbonaceous materials. , …”
Section: Results and Discussionmentioning
confidence: 99%
“…Activated carbon (AC) is widely used in gas storage, 1 food, and beverage processing, 2 as an adsorbent for air and water treatments, 3,4 metal recovery, 5 and medical treatments 6 . However, there is limited research on the application of AC for thermal energy storage 7,8 .…”
Section: Introductionmentioning
confidence: 99%